Linkage analysis of sex determination in Bracon sp. near hebetor (Hymenoptera: Braconidae). - Holloway, A K (2000)
To test whether sex determination in the parasitic wasp Bracon sp. near hebetor (Hymenoptera: Braconidae) is based upon a single locus or multiple loci, a linkage map was constructed using random amplified polymorphic DNA (RAPD) markers. The map includes 71 RAPD markers and one phenotypic marker, blonde. Sex was scored in a manner consistent with segregation of a single "sex locus" under complementary sex determination (CSD), which is common in haplodiploid Hymenoptera. Under haplodiploidy, males arise from unfertilized haploid eggs and females develop from fertilized diploid eggs. With CSD, females are heterozygous at the sex locus; diploids that are homozygous at the sex locus become diploid males, which are usually inviable or sterile. Ten linkage groups were formed at a minimum LOD of 3.0, with one small linkage group that included the sex locus. To locate other putative quantitative trait loci (QTL) for sex determination, sex was also treated as a binary threshold character. Several QTL were found after conducting permutation tests on the data, including one on linkage group I that corresponds to the major sex locus. One other QTL of smaller effect had a segregation pattern opposite to that expected under CSD, while another putative QTL showed a female-specific pattern consistent with either a sex-differentiating gene or a sex-specific deleterious mutation. Comparisons are made between this study and the in-depth studies on sex determination and sex differentiation in the closely related B. hebetor.